Magnitude and determinants of the ratio between prevalences of low vision and blindness in rapid assessment of avoidable blindness surveys - Kaphle, Dinesh (Division of Ophthalmology, 2016)
Part A of the dissertation includes the protocol of the study, which was approved by Faculty of Health Sciences Human Research Ethics Committee, University of Cape Town. The study was observational analytical, aiming to determine the magnitude and determinants of the ratio between prevalence of low vision and prevalence of blindness using Rapid Assessment of Avoidable Blindness (RAAB) surveys across World Bank regions. The surveys included in the study were available in the RAAB repository and obtained through permission from the primary investigators. A univariate and multivariate analysis were performed using the ratio as an outcome variable and potential explanatory variables as follows: prevalence of Uncorrected Refractive Error (URE), Cataract Surgical Coverage (CSC) at visual acuity 3/60, 6/60 and 6/18 for persons, logarithm of Gross Domestic Product per capita income and health expenditure per capita income. Part B contains the structured literature review. PubMed, Scopus, EBSCOHOST (Africa wide and MEDLINE) and Web of science databases were used to look for literature using the following key words: rapid assessment, blindness, age-related cataract, uncorrected refractive errors, low vision, visual impairment, avoidable OR curable OR preventable OR treatable. The summary of the literature review in addition to the gap in the literature is presented in the section. Part C includes a journal "ready" manuscript. The results showed that the ratio was between 1.35% in Mozambique and 11.03% in India. There was a statistically significant variation of the ratio across the regions: approximately 7.0 in South Asia and approximately 3.0 in Sub-Saharan Africa (X2=28.23, P<0.001). The variables: prevalence of Uncorrected Refractive Errors (URE), Cataract Surgical Coverage at visual acuity 3/60, 6/60 and 6/18 for persons, logarithm of Gross Domestic Product per capita and logarithm of health expenditure per capita were found to be statistically significantly associated with the ratio. However, only prevalence of URE and CSC at 3/60 for persons across the regions were found statistically significant in multivariate analysis.